Cost Estimation for Blasting and Painting Repair Work on KMP. Kormomolin - Nurul Hijrah Bahar; Taufiqur Rachman (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
One of the stages in the ship hull maintenance and repair process is the blasting and painting process. Parts of the ship hull that do not fulfill classification standards will be repaired to extend the ship's operational life. This study aims to estimate the material requirements and costs of blasting and painting in the ship hull repair process, so that the calculation of material requirements and repair costs can be used as a reference for ship owners in future repair activities. The methods used include data collection and repair of the KMP Kormomolin ship, as well as calculations of material usage efficiency based on the area worked on. Estimates of the requirements for each material are calculated based on the surface area of the ship and the efficiency of use per liter, then converted to cans or kilograms. The analysis results show that the main material requirements consist of copper slag as a blasting medium, as well as various types of coat such as primer, anti-corrosion (AC), anti-fouling (AF), and finishing coat. The total cost is calculated from the number of requirements multiplied by the unit price of the material. From the calculation results, it is known that the highest costs come from anti-fouling coat.